Evaluasi Proses Bisnis Material Management Berbasis Sap: Studi Kasus pada Perusahaan Consumer Goods - Yanti, Yanti; Zulfanahri, Zulfanahri; Yohanes, Meyli Monica; Monica, Vinsencia Vinny (ComTech: Computer, Mathematics and Engineering Applications, 2013)
This study analyzes and evaluates materials management processes running on a consumer goods company to find gaps between the needs of users and the SAP system used. This study aims to provide solutions and recommendations on the gap and to identify possible emerging risks. Analysis uses fit/gap Analysis. Itdescribes the evaluation results of the functions of SAP management material module used by the company. Therefore, we can identify what functions are not used optimally. Meanwhile, risk analysis method identifies the risks that can arise if the recommendations are not implemented. The results obtained from this study are recommendations and solutions that can be used by company to use SAP system function more optimally and in accordance with user?s needs. The conclusions that can be drawn is that the company must optimize the use of SAP system functions that have been implemented so that business processes can be run effectively and efficiently.